2017
DOI: 10.1175/waf-d-16-0203.1
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Hail Observations: Implications for NWS Warning Operations

Abstract: A field research campaign, the Hail Spatial and Temporal Observing Network Effort (HailSTONE), was designed to obtain physical high-resolution hail measurements at the ground associated with convective storms to help address several operational challenges that remain unsatisfied through public storm reports. Field phases occurred over a 5-yr period, yielding hail measurements from 73 severe thunderstorms [hail diameter ≥ 1.00 in. (2.54 cm)]. These data provide unprecedented insight into the hailfall character … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 39 publications
8
55
0
2
Order By: Relevance
“…For example, only maximum hail size is reported, and that value may be quantized or distorted by association to reference objects (e.g., golf balls). Recent high‐resolution hail observations from field campaigns [e.g., Ortega et al ., ; Blair et al ., ] suggest that larger hail sizes are more common than would be expected from Storm Data hail reports. Another characteristic of the Storm Data hail reports are positive trends in the frequency of hail in excess of 2 in.…”
Section: Introductionmentioning
confidence: 98%
“…For example, only maximum hail size is reported, and that value may be quantized or distorted by association to reference objects (e.g., golf balls). Recent high‐resolution hail observations from field campaigns [e.g., Ortega et al ., ; Blair et al ., ] suggest that larger hail sizes are more common than would be expected from Storm Data hail reports. Another characteristic of the Storm Data hail reports are positive trends in the frequency of hail in excess of 2 in.…”
Section: Introductionmentioning
confidence: 98%
“…If these storms were recorded as severe, rather than non‐severe, the random forest would be more adept at labelling pulse thunderstorms in these sections of data space, and overfitting would also probably relax. This possibility is reasonable in the light of recent studies using high‐resolution storm reports (Ortega et al, ; Blair et al, ). For instance, during the Hail Spatial and Temporal Observing Network Effort (HailSTONE) field project, Blair et al .…”
Section: Discussionmentioning
confidence: 97%
“…For instance, during the Hail Spatial and Temporal Observing Network Effort (HailSTONE) field project, Blair et al . () found that 32% of the severe‐hail‐producing storms sampled by field observers lacked a corresponding Storm Data report. Additionally, Storm Data hail diameters consistently under‐represented the maximum hail diameters sampled by the field team.…”
Section: Discussionmentioning
confidence: 99%
“…One parameter capable of identifying these storms is the supercell composite parameter (SCP; Thompson et al, 2003), which combines 0-6 km vertical wind shear (S06; m s −1 ), 0-3 km storm relative helicity (m 2 s −2 ), and surface-based convective available potential energy (J kg −1 ) into one convenient index that is skillful at statistically discriminating between supercell and nonsupercell environments. Supercells produce the vast majority of hailstones in excess of 5 cm in diameter (Blair et al, 2017), suggesting that such a proxy would be a useful metric for identifying favorable severe hail environments. This paper explores the influence of the GWO on hail frequency and intensity over the United States.…”
Section: 1002/2017gl076822mentioning
confidence: 99%
“…Previous research has indicated a relationship between the GWO and U.S. tornado frequency (Gensini & Marinaro, ; Moore, ). Since a majority of tornadoes are produced by supercell thunderstorms, it follows that variability in large hail frequency may also be explained by this metric, as large hail events are often an additional by‐product (Allen et al, ; Blair et al, ). Unlike tornadoes, few studies have considered the influence teleconnections on the frequency variability of damaging hailstones (Allen et al, ; Barrett & Henley, ; Lepore et al, ).…”
Section: Introductionmentioning
confidence: 99%